Variation of seed sizes and its effect on germination and seedling growth of mahogany (Swietenia macrophylla) - AGUS ASTHO PRAMONO; DIDA SYAMSUWIDA; Kurniawati Purwaka Putri (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Pramono AA, Syamsuwida D, Putri KP. 2019. Variation of seed sizes and its effect on germination and seedling growth of mahogany (Swietenia macrophylla). Biodiversitas 20: 2576-2582. To get high-quality seeds, the size of seed is often suggested to be criteria of selection in seed collection. However, the size is not always effective to be used as a basis for seed selection. The study is aimed to determine the variation of mahogany (Swietenia macrophylla) seed sizes and its effect on the germination and seedlings growth. The fruits were collected from stands of mahogany in Jonggol and Parung Panjang, Bogor District, Indonesia. The seeds were grouped into 5 classes based on seed size. The observation was conducted on seed viability of each size class as well as the growth of seedlings until 3 months old. The results showed that the seed size of mahogany was affected by position of the seeds inside the fruit, the mother trees, and fruit size. The seeds size of < 6 cm long had significantly lower germination rate and capacity than those seeds of more than 6 cm long. The size of seeds affected the initial growth of seedlings, but did not influence the subsequent growth of seedling after 3 months old. The selection of seeds was done by removing the seeds of less than 6 cm long.